Prometeu acorrentado? Um estudo empírico dos efeitos da desigualdade sobre o crescimento - Oliveira, Leonardo Gomes de (2009)
This work investigates the importance of income distribution on economic growth. We built a bigger and wider representative database of inequality than that commonly used in the literature. We use the system GMM estimator to estimate the parameters of interest. We found evidence of a negative relationship between inequality and growth when we use the more restrict database and evidence of a positive relationship between inequality and growth when we use the expanded one. The coefficients obtained indicate that inequality affects growth marginally.